New and Emerging Therapies for Uterine Fibroids - Fritton, Kate; Borahay, Mostafa A. (Seminars in Reproductive Medicine, 2017)
The pain, bleeding, and anemia associated with uterine fibroids debilitate many women. In addition to limited efficacy, the side effects of the currently used medical therapies prevent long-term use and nearly all pregnancies. Thus, women hoping to achieve pregnancy have limited options and usually opt for myomectomy. Once completed childbearing, many patients proceed with hysterectomy despite its risks and costs. Thus, there is a clear need for a new medical treatment for fibroids that is safe and effective. To this end, researchers have investigated several new treatments over the recent years, including both hormonal and nonhormonal ones. Some examples include selective progesterone receptor modulators, vitamin D, aromatase inhibitors, gene therapy, simvastatin, nanoparticles, epigallocatechin gallate, and intratumor collagenase injections. The aim of this article is to review and critically analyze the evidence (both laboratory and clinical) for these emerging therapies. We will discuss strengths and weaknesses of studies, areas where further evidence is needed, and finally deliberate on novel targets potentially amenable for development of future therapeutics.
Keywords: fibroids; leiomyoma; novel; treatment; therapy